Applications of upconversion nanoparticles in analytical and biomedical sciences: a review. Issue 14 (22nd June 2022) - Borse, Shraddha; Rafique, Rafia; Murthy, Z. V. P.; Park, Tae Jung; Kailasa, Suresh Kumar
Abstract : Upconversion nanoparticles have gained more attention due to their unique photon conversion capability from an incident wavelength to a more suitable emission wavelength at a designated site, thus improving their scope in analytical and biomedical sciences. Abstract : Lanthanide-doped upconversion nanoparticles (UCNPs) have gained more attention from researchers due to their unique properties of photon conversion from an excitation/incident wavelength to a more suitable emission wavelength at a designated site, thus improving the scope in the life sciences field. Due to their fascinating and unique optical properties, UCNPs offer attractive opportunities in theranostics for early diagnostics and treatment of deadly diseases such as cancer. Also, several efforts have been made on emerging approaches for the fabrication and surface functionalization of luminescent UCNPs in optical biosensing applications using various infrared excitation wavelengths. In this review, we discussed the recent advancements of UCNP-based analytical chemistry approaches for sensing and theranostics using a 980 nm laser as the excitation source. The key analytical merits of UNCP-integrated fluorescence analytical approaches for assaying a wide variety of target analytes are discussed. We have described the mechanisms of the upconversion (UC) process, and the application of surface-modified UCNPs for in vitro / in vivo bioimaging, photodynamic therapy (PDT), and photothermal therapy (PTT). Based on the latest scientific achievements, the advantages and disadvantages of UCNPs in biomedical and optical applications are also discussed to overcome the shortcomings and to improve the future study directions. This review delivers beneficial practical information of UCNPs in the past few years, and insights into their research in various fields are also discussed precisely.